O PRODETUR e a requalificação da Av. Beira-Mar de Fortaleza: avaliação de uma política de turismo e de suas expectativas socioeconômicas - Rios, José Gutemberg Frota (2015)
Public areas rehabilitation in the waterfront has been shown to be a global trend. The so-called “waterfront projects”, in general, are urban projects designed in a “Post-Fordist” prescription that is an urban policy of decentralization inducer and tertiary economic development (production and consumption), focusing on tourism activities as a way of attracting sound money resources, boosting the local economy and strengthening the city’s image. It is in this context that the Rehabilitation Project of Beira-Mar Avenue in Fortaleza-CE, an enlargement and valorization investment in a tourism multifunctional polo integrated to the metropolitan central core’s development dynamic fits. From the Northeast Tourism Development Program (Prodetur/NE) perspective, Beira-Mar Avenue rehabilitation project aims the tourism infrastructure improvement, integrating a set of actions for the historical, cultural and tourist valorization, implementing access facilities, new attractions, comfort and safety. Considering this scenario, this research aims to investigate and evaluate the Rehabilitation Project of Av. Beira-Mar in Fortaleza influence and its socioeconomic impact. The focus is to identify, from Prodetur/NE financing, prospects and future change possibilities in the economic and social dynamics of the new project licensees, especially to Craft Fair and Fish Market workers. It is considered the hypothesis that investments do not meet the interests of the workers, to the extent that the breeding values are intended primarily to infrastructure projects directly benefiting the tourist trade (the hotel and restaurant sectors) and the higher purchasing areas (A and B social classes). Thus, the socio-economic development to small traders and street vendors would be low and slow return.